Proceedings of the International Conference on Strongly Correlated Electron Systems (SCES2013) 2014
DOI: 10.7566/jpscp.3.013014
|View full text |Cite
|
Sign up to set email alerts
|

Weak Ferromagnetism in the Orthorhombic Perovskite SrIr0.8Sn0.2O3

Abstract: We present a comparative study on the structure, resistivity, and magnetic properties of a SrIrO 3 and a 20% Sn-doped SrIr 0.8 Sn 0.2 O 3 perovskite both stabilized under high-pressure and high-temperature conditions. We found that the substitution of isovalent, nonmagnetic Sn 4+ for Ir 4+ ions converts the ground state from a paramagnetic metal for SrIrO 3 to a weak ferromagnetic insulator with high transition temperature T c = 280 K for SrIr 0.8 Sn 0.2 O 3 . For the later compound, a temperature-driven condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Since the semimetallic ground state has been confirmed experimentally, it is of particular interest to achieve the proposed topological and/or magnetic states via tuning the SOC, U, and/or lattice symmetry. In this regard, Matsuno et al [45] of Pv SrIrO 3 to an antiferromagnetic insulator with a concomitant metal-insulator transition at T N [50]. These recent experimental efforts demonstrated that semimetallic Pv SrIrO 3 is a promising candidate for realizing distinct topological and magnetic insulating states that deserve further investigations in the near future.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Since the semimetallic ground state has been confirmed experimentally, it is of particular interest to achieve the proposed topological and/or magnetic states via tuning the SOC, U, and/or lattice symmetry. In this regard, Matsuno et al [45] of Pv SrIrO 3 to an antiferromagnetic insulator with a concomitant metal-insulator transition at T N [50]. These recent experimental efforts demonstrated that semimetallic Pv SrIrO 3 is a promising candidate for realizing distinct topological and magnetic insulating states that deserve further investigations in the near future.…”
Section: Physical Propertiesmentioning
confidence: 99%